2017
DOI: 10.1088/2053-1583/aa5921
|View full text |Cite
|
Sign up to set email alerts
|

Large-area synthesis of high-quality monolayer 1T’-WTe 2 flakes

Abstract: Large-area growth of monolayer films of the transition metal dichalcogenides is of the utmost importance in this rapidly advancing research area. The mechanical exfoliation method offers high quality monolayer material but it is a problematic approach when applied to materials that are not air stable. One important example is 1T’-WTe2, which in multilayer form is reported to possess a large non saturating magnetoresistance, pressure induced superconductivity, and a weak antilocalization effect, but electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 55 publications
3
61
0
Order By: Relevance
“…There has been some work on the bottom-up growth of nanoscale WTe 2 ; however, large-area and reproducible synthesis remains an open challenge [34,35]. Table 1 gives an overview of a range of publications that synthesised WTe 2 on the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been some work on the bottom-up growth of nanoscale WTe 2 ; however, large-area and reproducible synthesis remains an open challenge [34,35]. Table 1 gives an overview of a range of publications that synthesised WTe 2 on the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 gives an overview of a range of publications that synthesised WTe 2 on the nanoscale. Chemical vapour deposition (CVD) growth of WTe 2 has achieved single-crystal monolayers with lateral dimensions on the order of tens to hundreds of micrometres from Te, WO 3 and WCl 6 precursors [34,35,40]. Despite requiring high growth temperatures, 650-800 °C, CVD growth remains the most promising method for highquality monolayer synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Naylor et al presented an accessible CVD method to fabricate monolayer 1T’-WTe 2 flakes, and the surface coverage of this method was around 20%. They also suggested that the degradation of WTe 2 could be averted by reducing the handling time and introducing few-layer graphene onto the substrate instantly after the reaction to passivate the WTe 2 [ 44 ]. There are two stacking sequences in the bilayer WTe 2 , and low-temperature transport measurements indicate a semimetal–insulator transition, as mentioned [ 45 ].…”
Section: Preparation Of Wtementioning
confidence: 99%
“…In the group of materials that can be exfoliated into monolayers and that have been predicted to be QSHI are the 1T ′ polytypes of some transition metal dichalcogenides, with scanning tunneling microscopy work detecting edge states for WTe 2 , MoS 2 , and WSe 2 . From these, MoS 2 and WSe 2 are unstable and tend to convert to the 2H phase, whereas WTe 2 quickly oxidizes in air . These issues make clear the urgency for the search and characterization of new stable materials with convenient structures to be applied as QSHIs and 3D topological insulators.…”
Section: Introductionmentioning
confidence: 99%